2011
DOI: 10.1155/2011/373197
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Temperament, Stress, and Immune Function in Cattle

Abstract: The detrimental effects caused by stressors encountered by animals during routine handling can pose economic problems for the livestock industry due to increased costs ultimately borne by the producer and the consumer. Stress adversely affects key physiological processes of the reproductive and immune systems. In recent years stress responsiveness has been associated with cattle behavior, specifically temperament. Cattle with more excitable temperaments, as measured by chute score, pen score, and exit velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 69 publications
5
94
1
14
Order By: Relevance
“…Several studies have shown that calm cattle have lower basal levels of catecholamines and serum cortisol than flighty cattle (Burdick, et al, 2010a;Burdick, et al, 2010b;Burdick, Randel, Carroll, & Welsh, 2011;Vann, et al, 2010). Gruber, et al (2010) also demonstrated that epinephrine levels at slaughter were lower in calm cattle.…”
Section: Effect Of Flight Speed On Plasma and Muscle Lactatementioning
confidence: 99%
“…Several studies have shown that calm cattle have lower basal levels of catecholamines and serum cortisol than flighty cattle (Burdick, et al, 2010a;Burdick, et al, 2010b;Burdick, Randel, Carroll, & Welsh, 2011;Vann, et al, 2010). Gruber, et al (2010) also demonstrated that epinephrine levels at slaughter were lower in calm cattle.…”
Section: Effect Of Flight Speed On Plasma and Muscle Lactatementioning
confidence: 99%
“…Ante la presencia de muchos estresores, el SNS es activado a través de neuronas noradrenérgicas en el cerebro y de neuronas simpáticas postganglionares que inervan los órganos periféricos (ejemplo: Corazón, vasculatura, riñones, intestino y tejido adiposo), secretando de esta forma norepinefrina dentro de la circulación, que aumenta la presión sanguínea y las frecuencias cardiaca y respiratoria (Burdick et al, 2011).…”
Section: Sistema Nervioso Simpático (Sns)unclassified
“…Estos factores estresantes alteran la homeostasis en el animal, provocando una respuesta adaptativa que es activada en un intento por restaurar el balance a través de una serie de mecanismos fisiológicos que involucran el eje Hipotalámico-Hipofisiario-Adrenal (Moberg, 2000) y dependiendo de la magnitud del estímulo, duración e intensidad de los estresores y la susceptibilidad de los animales hacia ellos, se puede presentar inhibición del sistema inmunológico que predispone posteriormente a que se afecte la fisiología durante el crecimiento y la reproducción en los bovinos (Burdick et al, 2011;Fell et al, 1999).…”
Section: Introductionunclassified
“…In this sense, a previous study showed that hostile animals have lower reproductive performance (Phocas et al, 2006). Moreover, it has been suggested that the main cause of this lower reproductive performance is the greater basal concentrations of glucocorticoids and catecholamines shown in more temperamental cattle, leading to a "stress like" situation (Burdick et al, 2011). Likewise, high genetic selection pressure only for a few specific production traits might have the same deleterious effect on reproductive traits, as it has been demonstrated in high-producing dairy cows (Walsh et al, 2011).…”
mentioning
confidence: 97%